2002
DOI: 10.1063/1.1461065
|View full text |Cite
|
Sign up to set email alerts
|

Domain walls in ferromagnetic nanoconstriction

Abstract: 180° domain walls in ferromagnetic nanoconstrictions are investigated by classical atomic Monte Carlo simulations. Two types of constrictions are considered; one is a uniform circular cylinder (isthmus), the other is a double-truncated cone (hour glass). The wall width is determined by the effective length of the constriction, which may be as little as a nanometer. The wall can have a Néel-like configuration for constrictions much narrower than the normal wall width, but there is a crossover region with vortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Monte Carlo simulations of the magnetisation in nanocontacts confirm Bruno's idea of a constrained wall and showed the possibility of thermal fluctuations in the form of walls in a nanocontact between various different Bloch, Néel, and vortex states [331]. They estimate the height of the energy barrier separating these states as equivalent to about 80 mK per atom, meaning that structures smaller than about 10 nm in size will be unstable at room temperature [332].…”
Section: Theoretical Interpretationmentioning
confidence: 50%
“…Monte Carlo simulations of the magnetisation in nanocontacts confirm Bruno's idea of a constrained wall and showed the possibility of thermal fluctuations in the form of walls in a nanocontact between various different Bloch, Néel, and vortex states [331]. They estimate the height of the energy barrier separating these states as equivalent to about 80 mK per atom, meaning that structures smaller than about 10 nm in size will be unstable at room temperature [332].…”
Section: Theoretical Interpretationmentioning
confidence: 50%
“…Coey et al concluded [29,30] that giant MR of a nanocontact may be reduced somewhat by these fluctuations, but not eliminated. In recent calculations Zhuravlev et al [31] also predicted giant values and fluctuations of MR in segmented nanowires, when conductance of the wire is quantizes.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…24 While this model is certainly oversimplified, it can explain why no huge ballistic magnetoresistance is observed in this type of contact. Atomic Monte Carlo 25 and micromagnetic 26,27 simulations of different nanocontacts and nanoconstrictions indicate that there are vortex modes in small constrictions. Our own OOMMF simulations ͑Fig.…”
Section: ͑Nm͒ ͑2͒mentioning
confidence: 99%